ASPEK SOPAN SANTUN UJARAN DALAM FILM EAT PRAY LOVE KARYA RYAN MURPHY (Analisis Pragmatik) - Ismet, Mohamad Nawir (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This study is an attempt to identify and analyze the politeness aspects which are found in the film Eat Pray Love. In this research, the writer focuses on the polite utterance as one aspect of behavior which is found in the film Eat Pray Love. .Â Â Â Â Â Â Â Â Â Â This research was done through the descriptive method. In collecting the data, the writer paid close attention to the available relevant data through conversation among the characters in the film. Then the writer categorized them into their suitable maxims using the concept of Leech. The finding shows that the uses of politeness maxims in the film are tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. It is expected that this study can help the students and readers in learning politeness aspects of using language. Keywords: politeness aspects, maxims, Film â€œEat Pray Loveâ€.